Identification of physical changes in dome house (Teletubies) Ngelepen Dusun, Prambanan with the Post Occupancy Evaluation (POE) approach - Budiharjo, Rachmat; Leksono, Soesilo Boedi (ARTEKS : Jurnal Teknik Arsitektur, 2024)
A relocation of houses for the residents of Sengir hamlet, approximately 500 meters away from Nglepen hamlet, which was affected by the earthquake in 2006, the Dome House (Teletubbies) is the product of the participation of several donor countries and is located in Nglepen hamlet, Sumberharjo Village, Kapanewon Prambanan, Sleman Regency, Special Region of Yogyakarta. It has caused its people many contentious issues since it was first used in April 2007. In 2016, the region received the nickname "Dome House Tourist Village (Teletubbies), Nglepen - Prambanan" until 2018, when the community began to relive the glory era. There has been a decrease in tourist visits thus far as a result of the COVID-19 outbreak in 2019–2021. This condition is exacerbated by the addition of space that is not integrated with the dome house plan and changes in the face of the building, further reducing the performance (uniqueness) and attractiveness of the house itself. For this reason, the "Post Occupancy Evaluation (POE)" research was carried out to determine the process of changes to the dome house.